FROM SOIL TO TABLE: EVALUATING CONVENTIONAL AND ECOLOGICAL CULTIVATION SYSTEMS IN SOUTH-WEST OLTENIA, ROMANIA - Cosmina SMEDESCU; Dragoș SMEDESCU; Alina MĂRCUȚĂ; Liviu MĂRCUȚĂ; Valentina Constanța TUDOR (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the context of rising concerns about sustainability and environmental impact, this article focuses on analyzing two remarkable agricultural systems in the South-West Oltenia Development Region: the conventional and the ecological, and emphasizes one of the foundational crops for the region, wheat. The research was derived from a comprehensive questionnaire applied on 18 farms in the South-West Oltenia region: half of them employing ecological practices and the other half using conventional methods. Our primary focus was to determine the most economically viable agricultural system for the area. Through this analysis, the article not only illustrates the evolution of this crop's production from 2020 to 2022, but also provides insights into production costs and their valorization in the market. Moreover, it underscores the importance and advantages of each agricultural system, highlighting potential long-term benefits from both economic and sustainable perspectives. To provide a solid and well-grounded analysis, statistical methods were employed, combined with data obtained fromthe questionnaire administered directly at the farm level in the region. This methodology offers a clear perspective on the profitability and efficiency of the two agricultural systems in the specific context of South-West Oltenia.